Solar quiet current and conductivity-depth profiles of the earth mantle from quiet-time geomagnetic field records in Asia Sub-Region / Mustapha Abbas - Mustapha , Abbas (2018)
This study investigate the month-by-month behavior of the external and internal ionospheric current system, their quiet fields and the conductivity-depth profile of Asia sub-region using selected geomagnetic field records from dip minimum to moderate solar activity years. The separation of the external and internal field contributions to the Sq variations was successfully carried out using spherical harmonic analysis (SHA). A transfer function was then employed to determine the conductivity profile to a depth of about 800 km from the paired external and internal coefficients of the SHA. The results reveal that the daytime external, internal and sum of the quiet fields for the horizontal and vertical components equatorward and poleward of the Sq focus exhibit daytime positive and negative amplitudes with the former increasing (decreasing) with increasing solar activity (latitudes) while the latter increases with increasing latitudes but show no linear relationship with increasing solar activity. Throughout the years, the external quiet field magnitudes are about twice larger than their corresponding internal and both exhibit slight phase variations that are believed to arise from electromagnetic induction effect. The external and internal equivalent currents contours are characterized by a single daytime vortex near mid-latitudes that linearly increased from the strong summertime amplitudes reaching ~-10.5 ×104A during the dip minimum solar activity year 2008 to about 11.7 × 104 and 15.5 × 104A during low and moderate solar activity years 2017 and 2012 and the internal Sq current vortices are only about 0.8, 0.56 and 0.50 times as large in 2008, 2017 and 2012. The internal equivalent current vortices in winter months disappeared more frequently than the external and the disappearance of both external and internal current vortices decreases with increasing solar activity. The internal currents foci mostly appeared slightly poleward than the external foci. At low latitudes there seems to be intrusion of stronger summertime current vortex of the opposite hemisphere into the winter hemisphere appearing most frequently during the pre-noon hours in the southern hemisphere and in the afternoon hours in the northern hemisphere. A regression line fitted to the estimated conductivity values show a downward increase in electrical conductivity with depths beneath this region. At depths range ~130 and 300 km, the profile showed an evidence of increase in conductivity followed by a sharp steep increase in conductivity profile at depth of about 310, 350 and 410 km in 2008, 2012 and 2017. Generally the increase in conductivity profile appeared more rapid during the moderate solar activity year 2012 and slower in 2017 and 2008. The profiles have not shown any significant variations in their depth of penetration despite major differences in their annual sunspot numbers, but the higher and rapid increase in conductivity profile in 2012 could be the effect of difference in solar activity. The profiles thus indicates that there may likely be major lateral heterogeneity in the electrical conductivity of the Earth’s upper mantle.